2008
DOI: 10.1590/s1519-38292008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção da transmissão vertical do vírus da imunodeficiência humana: análise da adesão às medidas de profilaxia em uma maternidade de referência em Fortaleza, Ceará, Brasil

Abstract: OBJETIVOS: avaliar a adesão às medidas de profilaxia da transmissão vertical do HIV em parturientes infectadas pelo HIV que receberam atendimento em uma maternidade de referência na cidade de Fortaleza, Estado do Ceará, Brasil. MÉTODOS: estudo transversal, com componentes descritivos e analíticos. Foram incluídas todas as parturientes com infecção pelo HIV admitidas na maternidade no período de janeiro de 2000 a agosto de 2004. RESULTADOS: participaram 110 parturientes infectadas pelo HIV, sendo que 102 (92,7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 8 publications
2
6
0
11
Order By: Relevance
“…In addition, other studies with seropositive women revealed a higher prenatal coverage than that found in our study, with percentages between 92.7% and 97.7%. (4,5) The prevalence of cesarean deliveries found in our study is compatible with other studies. In such cases, professionals based the procedure on guidelines issued by the Brazilian Ministry of Health on elective labor; however, this type of delivery should not be a rule because seropositive women can also undergo vaginal delivery, depending on clinical and obstetric conditions of the case.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, other studies with seropositive women revealed a higher prenatal coverage than that found in our study, with percentages between 92.7% and 97.7%. (4,5) The prevalence of cesarean deliveries found in our study is compatible with other studies. In such cases, professionals based the procedure on guidelines issued by the Brazilian Ministry of Health on elective labor; however, this type of delivery should not be a rule because seropositive women can also undergo vaginal delivery, depending on clinical and obstetric conditions of the case.…”
Section: Discussionsupporting
confidence: 92%
“…(3,4) A high proportion of diagnoses of HIV infection among pregnant women was observed during prenatal visits (49.49%), a finding that corroborates results of other studies. (5,6) An increase in the number of seropositive pregnant women during prenatal visits was observed throughout the years. This increase reveals important data because the prenatal visit is often one of the only times that the women present to health service.…”
Section: Discussionmentioning
confidence: 99%
“…The sociodemographic profile was similar to that found in other studies 16,17 , in which patients with lower education levels may have reduced quality of prenatal care. If there was prior knowledge of HIV positivity, there was a more effective reduction in vertical transmission 18 . In 10.9% of pregnant women, the diagnosis occurred during delivery, meaning a missed opportunity for preventive intervention during the prenatal period.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study in Sergipe, 42.1% of pregnant women attended fewer than six consultations 11 , a similar rate to that found in this survey (44.5%). This inadequate attendance led to inadequate testing for HIV (12.8%) and syphilis (11.8%), demonstrating poor quality prenatal care 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Esse panorama foi encontrado entre 110 mulheres de Fortaleza. Embora 45 conhecessem a sua serologia antes do pré-natal, 57.3% (n=63) descobriram a infecção durante o pré-natal e duas delas somente no parto (Cavalcante, Silveira, Ribeiro, & Ramos Jr., 2008). Ressalta-se que o momento de descoberta do diagnóstico reveste-se de importância, haja vista os cuidados de que a dupla mãe-bebê necessita para evitar a transmissão vertical.…”
Section: Sentimentos Despertados Pelo Diagnóstico Da Infecção Pelo VIunclassified